New Challenges in Communication with Cancer Patients - Surbone, Antonella; Zwitter, Matjaž; Rajer, Mirjana; Stiefel, Richard (Springer US : Imprint: Springer, 2013)
The relationship between oncologists and their cancer patients is rapidly evolving. Oncologists and other cancer professionals master new anticancer and supportive treatment options, while working under increasing economic pressure and time constraints, and are often unprepared to deal with all the challenges of their new position in a therapeutic relationship with cancer patients and families. Good communication is as essential as are modern laboratory tests and sophisticated diagnostics to achieve the best clinical results. This book updates the evolution of truth-telling and communication patterns worldwide and offers insights into the recent trends and emerging challenges in communication with cancer patients and families. New Challenges in Communication with Cancer Patients is an invaluable resource to medical professionals, educators and patients in establishing a strong and effective partnership built on trust and mutual understanding.